Improving Learning Outcomes and Science Process Skills Through the Project Based Learning (PJBL) Model Class IV SDN 2 Suroyudan - Ika Ovita (Universitas Sebelas Maret, 2020)
This study aims to improve learning outcomes and science process skills on the Always Saving Energy Theme through the Project Based Learning (PJBL) learning model in class IV Semester 1 SD Negeri 2 Suroyudan. The subjects in this study were fourth grade students of SD Negeri 2 Suroyudan, totaling 32 students. This research is a Classroom Action Research conducted in two cycles in each cycle consisting of two meetings. Each cycle includes planning, implementing actions, observing and reflecting. The research data were analyzed using quantitative data analysis. To obtain data on students' science process skills, they used observation sheets and science process skills questionnaires, while to obtain data on learning outcomes in this study, the evaluation sheets were given in each cycle. Based on the results of the study, students' science process skills in cycle 1 were 34%, increased to 94% in cycle 2. student learning completeness in cycle 1 was 75% with an average class of 80 increased to 100% with a class average of 92.81 in cycle 2. From these results, it can be concluded that through the application of learning with the Project Based Learning (PJBL) model can improve learning outcomes and science process skills on the Always Saving Energy Theme in class IV Semester 1 SD Negeri 2 Suroyudan in 2019/2020.